2022
DOI: 10.1182/bloodadvances.2021006398
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte cytosolic protein 1 (L-plastin) I232F mutation impairs granulocytic proliferation and causes neutropenia

Abstract: Neutrophils migrate into inflamed tissue, engage in phagocytosis, and clear pathogens or apoptotic cells. These processes require well-coordinated events involving the actin cytoskeleton. We describe a child with severe neutropenia and episodes of soft tissue infections and pneumonia. Bone marrow examination showed granulocytic hypoplasia with dysplasia. Whole exome sequencing revealed a de novo heterozygous missense mutation in LCP1, which encodes the F-actin binding protein Lymphocyte Cytosolic Protein 1. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Ning et al found that LCP1 was upregulated and acted as a specific molecular marker of cancer recurrence and therapeutic targets in colon cancer [ 25 ]. Similarly, LCP1 was confirmed to promote the cell invasion and metastasis in prostate cancer cells, and the silencing experiment indicated that LCP1 might be an effective approach for tumors treatment [ 5 , 22 ]. On the other hand, Wen et al [ 11 ] performed a global proteomic analysis to explore the differently expressed genes in the cerebral ischemia–reperfusion injury through MCAO rat model.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ning et al found that LCP1 was upregulated and acted as a specific molecular marker of cancer recurrence and therapeutic targets in colon cancer [ 25 ]. Similarly, LCP1 was confirmed to promote the cell invasion and metastasis in prostate cancer cells, and the silencing experiment indicated that LCP1 might be an effective approach for tumors treatment [ 5 , 22 ]. On the other hand, Wen et al [ 11 ] performed a global proteomic analysis to explore the differently expressed genes in the cerebral ischemia–reperfusion injury through MCAO rat model.…”
Section: Discussionmentioning
confidence: 99%
“…As an actin-binding protein, Lymphocyte cytosolic protein 1 (LCP1) regulates cell movement mainly by interacting with actin, and is one of the main cytoskeleton binding proteins that directly control cell movement [ 5 ]. In addition, LCP1 is also involved in host defense, the formation of immune synapses, T cell activation, etc.…”
Section: Introductionmentioning
confidence: 99%
“…CX3CR1 , which serves as receptors for fractalkine, is important for the adhesion and migration of leukocytes (32), and considered to be a potential therapeutic target among septic patients (33). LCP1 encodes for lymphocyte cytosolic protein 1 and is involved in granulopoiesis (34) as well as activation of T cells (35). SHCBP1 encodes for SH2 domain binding protein 1 and is implicated in CD8+ T cell function (36).…”
Section: Discussionmentioning
confidence: 99%